A Symmetric Encryption Method for Transmitting IEC 62351 Communicaiton Keys in Substations - Fang FANG; Guanghua LI; Donghui WANG; Xiaohua XUAN (Zhongguo dianli)
With the improvement of the information level of the substation, the cyber security problem of information communication has become increasingly prominent. The authentication encryption-based network security solution, such as the IEC 62351 standard, needs to transmit the application keys through another special secure transmission channel. This paper creatively proposes a method to build a secure transmission channel of application encryption keys through communication key negotiation mechanism under symmetric encryption. Based on the advanced encryption standard algorithm and symmetric key group, this method realizes the communication key negotiation mechanism through the combination of initial key and random number. The negotiated key has the character of randomness, which solves the possible security risk caused by using the same key for all links of traditional symmetric encrypted communication. In this paper, the corresponding technical analysis is also carried out, which include anti-replay, encryption strength, and anti-key theft attack, etc. The method is good in security and convenient for use, and can provide reference for key transmission of intelligent substation cyber security system.